2021
DOI: 10.1016/j.jaci.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental immunophenotyping in COVID-19 ARDS: A case series

Abstract: Background Severe immunopathology may drive the deleterious manifestations that are observed in the advanced stages of coronavirus disease 2019 (COVID-19) but are poorly understood. Objective Our aim was to phenotype leukocyte subpopulations and the cytokine milieu in the lungs and blood of critically ill patients with COVID-19 acute respiratory distress syndrome (ARDS). Methods We consecutively included patients less than 72 hours after intu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 37 publications
(41 reference statements)
6
79
1
Order By: Relevance
“…Other coronavirus such as severe acute respiratory syndrome CoV (SARS-CoV) and Middle East respiratory syndrome CoV (MERS-CoV) may also produce an acute lung injury associated with an exaggerated pro-inflammatory cytokine/chemokine systemic response [ 26 ]. In COVID-19 ARDS patients, a recent study has demonstrated a severely hyperinflammatory milieu in both the lungs and peripheral blood but characterised by activated lymphocytes in low numbers, a specific immunologic profile was identified in the lungs, consisting of a depleted and exhausted CD4 and CD8 T cell population prevailing those subtypes involved in both reparative and destructive processes [ 27 ].…”
Section: Systemic Inflammatory Syndromes Related To Covid-19mentioning
confidence: 99%
“…Other coronavirus such as severe acute respiratory syndrome CoV (SARS-CoV) and Middle East respiratory syndrome CoV (MERS-CoV) may also produce an acute lung injury associated with an exaggerated pro-inflammatory cytokine/chemokine systemic response [ 26 ]. In COVID-19 ARDS patients, a recent study has demonstrated a severely hyperinflammatory milieu in both the lungs and peripheral blood but characterised by activated lymphocytes in low numbers, a specific immunologic profile was identified in the lungs, consisting of a depleted and exhausted CD4 and CD8 T cell population prevailing those subtypes involved in both reparative and destructive processes [ 27 ].…”
Section: Systemic Inflammatory Syndromes Related To Covid-19mentioning
confidence: 99%
“…Interestingly, soluble CD25 was increased in the peripheral blood of COVID-19 patients, while its ligand IL-2 was also increased [3,52]. In mechanically ventilated COVID-19 patients with ARDS, in sharp contrast to the lymphopenia in both subsets of CD4 and CD8 T cells, the proportion of Treg cells (defined by CD4 + FoxP3 + ) was increased in the lungs and peripheral blood mononuclear cells (PBMC) [53]. The degree of Treg recruitment into the lungs of COVID-19 patients may determine the severity of the disease since patients with more Treg cells experienced milder disease [54,55].…”
Section: The Role Of Tregs In the Immunopathology Of Covid-19: Currenmentioning
confidence: 99%
“…Another immune mechanism, which is probably important regardless of whether a type 3 reaction takes place, is the highly proinflammatory cytokine response to SARS-CoV-2, which is prominent both in milder and very severe cases, and which some have designated a “cytokine storm” ( 18 , 19 ). This involves vast elevations in the classical pro-inflammatory cytokines, TNF-α and IL-1β, which have prominent effects on the endothelium.…”
Section: Covid-19 Is (Also) a Vascular Diseasementioning
confidence: 99%